Case Method Learning for Stimulating 21st Century Skills of PG PAUD Students in Educational Management Courses - Fitriana, Septi; Ardina, Mona; Indrawati, Indrawati (Riwayat: Educational Journal of History and Humanities, 2025)
This research aims to look at case method learning in stimulating 21st Century skills of PG PAUD students in education management courses. This research is very important to carry out in order to see the success of PG PAUD FKIP Study Program students at Bengkulu University in accordance with IKU 7 collaborative and participatory classes. This research method is qualitative research, namely; One class of educational management courses consists of 26 students. The research instrument uses direct observation sheets, interviews and documentation. This research was conducted in May-October 2024. The results of this research show that through case method learning students have 21st century skills, namely; critical thinking, creativity, communication, and collaboration. It can be concluded that case method learning can be carried out in education management courses.